A Religião que a Modernidade Produz: Sobre a História da Política Religiosa na França - Giumbelli Emerson (Dados: Revista de Ciências Sociais, 2001)
This article discusses several aspects of the history of religious policy in France, focusing on realities from the 16th to 20th centuries involving the ways by which the state deals with "religion". The objective is to show that far from simply being overlooked, "religion" takes on meanings that make it a significant criterion for social ordering from the state perspective. One can thus affirm that the French state has promoted several successive forms of recognizing religious identities. French history appears here in light of a more general discussion on the place and statute of religion in modernity. Reflecting on certain points in the "secularization thesis", the article concludes by highlighting aspects that indicate a positive relationship between modernity and religion.